Um olhar acerca da tecnologia no teatro de rua: a tecnologia como meio de ação, mediando saberes, processos e fazeres humanos - Sugayama, Soraya (2012)
This work presents a social-historical approach and it aims to reflect upon the street theater. This work discusses technology as a mediator of the knowledge, processes and human activities. It works with the Certeau’s principle that treats space as Practice’s Space and approaches the subjects as bearers of responsible and responsive qualities. Therefore, it considers the subjects existence as given by the relation or response to others. Aiming to think on technology on street theaters, this research presents observations and interview transcriptions performed with two street theater groups from Curitiba-PR. This work dialogues with Technology, Theater, Linguistics, Communication and Culture areas together with STS studies and other areas. This work’s main objective is to perceive and comprehend the relations, processes and performing art which generates poetics thinking technology as a mean of action, that connects processes and means of and ways to make people. Another objective is let the researched groups speak, aiming to understand the researched object mediated by these artists speech on the “materiality” presented in scene.